2018
DOI: 10.2500/aap.2018.39.4114
|View full text |Cite
|
Sign up to set email alerts
|

Association of alopecia areata with atopic dermatitis and chronic spontaneous urticaria

Abstract: An estimated prevalence of AA among an Israeli population was ∼0.8%. The novel finding of our study was the high prevalence of food allergy and CSU in patients with AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 0 publications
1
21
0
3
Order By: Relevance
“…The prevalence of asthma in hair loss patients ranged from 9.9 to 10.3%, compared to 6.5–7.7% for controls ( p ≤ 0.001–0.064) [27, 28]. No statistical association was identified in 4 other case-control studies (4,918 AA patients and 784,330 control patients) [21, 28-30].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The prevalence of asthma in hair loss patients ranged from 9.9 to 10.3%, compared to 6.5–7.7% for controls ( p ≤ 0.001–0.064) [27, 28]. No statistical association was identified in 4 other case-control studies (4,918 AA patients and 784,330 control patients) [21, 28-30].…”
Section: Resultsmentioning
confidence: 99%
“…A significant association was found between family history of atopy and allergic disorders and AA, with 28% of AA patients reporting a positive family history compared to 4% of controls ( p = 0.046) [21, 27-30]. Three cross-sectional studies regarding asthma and hair loss with a total 1,600 patients reported the prevalence of asthma among AA patients of 1.34–14.5%; however there was no reported association with early onset of AA or development of alopecia totalis or universalis [20, 31, 32].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations